Modal analysis on different type of aluminium, joined by tig welding - Aziee Edna Diawati, Hazwan (2013)
Experimental Modal Analysis and Finite Element Analysis will be used to study the dynamic characteristic of a TIG welded joint between aluminium 1100 and aluminium 6061. The structural three-dimensional solid modelling of joining between aluminium 1100 and aluminium 6061 by TIG welding was developed using the SOLIDWORK drawing software. The finite element analysis was then performed in ALGOR software. The finite element model of the components was analyzed using the linear modal analysis approach and the experimental modal analysis was performed by using an Impact Hammer. Finally, an operating deflection shape analysis was carried out to investigate the dominant mode shape under a given operating condition. The natural frequency of the mode shape is determined and comparative study of modal analysis and finite element analysis was done from both method results. The comparison between natural frequencies of finite element modelling and model testing shows the closeness of the results. From the results, the percentage error had been determined. The percentage error is bit high because there are some errors occur during the experimental modal analysis. The experimental modal analysis is conducted with free boundary condition and the effect of damping which effect test rig by using sponge as a base of the plate is a factors as the higher percentage error. The result from the operating deflection shape analysis shows that mode two is the dominant mode shape with an operating frequency of 581 Hz.